Out of the Contemplation on the Law: An Attempt at Outlining Some Problems - Kaźmierczyk, Stanisław (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
The author addresses the problem of the cognitive role of intellectual processes in the sphere of intellectual objects, which also include the established law. Only by virtue of intellectual processes focused on the law can it be cognitively made available to others. Contrary to conceptualists, and above all Kelsen, it is then necessary to move away from determining the doctrine of law with a conceptual grid, as the basic undertaken means of controlling the legal issues. It cannot be accepted that what is not verifiable in such a grid cannot be treated as a heuristic attitude towards the law. The author distinguishes the so-called high interpretation, which has the characteristic that it consists in the course of the entire law, including the development of legal thought on the law and the consequences of the law. There is no such thing as the development of law in its empirical sense. On the other hand, thinking about it through interpretation, properly combined with interpretation at a high level, contemplating it by combining legal considerations with interpretation at a high level should, in the Author’s opinion, be considered the deepest manifestation of the reflexivity of legal culture.